2017
DOI: 10.3389/fnmol.2017.00303
|View full text |Cite
|
Sign up to set email alerts
|

PLPP/CIN Regulates Seizure Activity by the Differential Modulation of Calsenilin Binding to GluN1 and Kv4.2 in Mice

Abstract: Calsenilin (CSEN) binds to Kv4.2 (an A-type K+ channel) as well as N-methyl-D-aspartate receptor (NMDAR), and modulates their activities. However, the regulatory mechanisms for CSEN-binding to Kv4.2 or NMDAR remain elusive. Here, we demonstrate the novel role of pyridoxal-5′-phosphate phosphatase/chronophin (PLPP/CIN), one of the cofilin-mediated F-actin regulators, in the CSEN binding to Kv4.2 or GluN1 (an NMDAR subunit). PLPP/CIN dephosphorylated CSEN in competition with casein kinase 1, independent of cofil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 52 publications
4
22
0
Order By: Relevance
“…Recently, we have reported that PLPP/CIN −/− mice show the shorter latency of seizure onset, but interrupt seizure progression in response to KA 30 . In contrast, spontaneous NEDD mutation in NEDD4-2 andi mice increases seizure susceptibility in response to KA 14 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, we have reported that PLPP/CIN −/− mice show the shorter latency of seizure onset, but interrupt seizure progression in response to KA 30 . In contrast, spontaneous NEDD mutation in NEDD4-2 andi mice increases seizure susceptibility in response to KA 14 .…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, spontaneous NEDD mutation in NEDD4-2 andi mice increases seizure susceptibility in response to KA 14 . Since 2h after KA injection is the suitable time point to compare the time of seizure onset, total EEG power and the changes in anatomical or biochemical profiles in PLPP/CIN Tg and PLPP/CIN −/− mice 30 , we investigated whether PLPP/CIN-mediated NEDD4-2 ubiquitination reciprocally regulates seizure activity 2 h after KA injection. Consistent with our previous report 30 , PLPP/CIN deletion reduced the latency of seizure onset, seizure intensity (severity), and seizure duration in response to KA ( p < 0.05 vs. WT mice, respectively; Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…EEG signals were digitized and analyzed using LabChart Pro v7 (AD Instruments, Australia). Spectrograms were automatically calculated using a Hanning sliding window with 50% overlap ( Kim et al, 2016 , 2017b ).…”
Section: Methodsmentioning
confidence: 99%
“…The hippocampal tissues were lysed in radioimmune precipitation buffer (RIPA) with protease and phosphatase inhibitor cocktails (Roche Applied Sciences, United States) and 1 mM sodium orthovanadate. After calibration of total protein concentrations, and equal amounts of proteins were precipitated with the primary antibody and subsequent protein G sepharose at 4°C overnight ( Kim et al, 2017b ). Beads were collected, eluted in sample buffer and boiled at 95°C for 5 min.…”
Section: Methodsmentioning
confidence: 99%